Sedimentology and stratigraphy of the La Providencia Group (nov. nom.): upper Neoproterozoic cover, Tandilia System, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Neoproterozoic sedimentary cover of the Río de La Plata Craton in the Sierras Bayas - Olavarría region, located in the northwestern sector of the Tandilia System, is represented by the Sierras Bayas Group (Villa Mónica, Cerro Largo, Olavarría and Loma Negra formations; Fig. 1), which is unconformably overlain by the Cerro Negro Formation (Poiré and Spalletti, 2005). The Sierras Bayas Group is composed of a variety of different marine sedimentary rocks which are characterized by the absence of strong deformation and metamorphism (Gómez Peral et al., 2007). Compared to the Sierras Bayas Group, the Cerro Negro Formation received less attention over the last years. In the Sierras Bayas region (Fig. 2), Iñiguez and Zalba (1974) and Iñiguez et al. (1989) described and named this unit in well-exposed quarries faces. They indicated that it was mostly composed of siliciclastics (reddish mudstones and sandstones), with subordinated marls in its basal section. In the nearby subsurface area, some authors mentioned the presence of a relatively thick succession of dark fine-grained rocks overlying the Sierras Bayas Group (Amos et al., 1972; Cuomo et al., 1983), but the relationship with the Cerro Negro Formation described in outcrops was unclear. The aim of this contribution is to present the sedimentological attributes and stratigraphic relationships of the outcrop and subsurface successions originally reported as Cerro Negro Formation, in order to integrate this upper section of the Neoproterozoic cover in a common evolutionary model. To do so, more than 200 m of cores were described (Fig. 3), and combined with sections measured in the quarries. Conventional sedimentological description (textures, physical structures, bed thickness, etc.), was combined with X-Ray diffraction and standard petrography, in order to define mineralogical composition and proportion of main components. In this context, 181 samples were analyzed by XRD using standard procedures, and 50 thin sections, mostly from siltstones and sandstones, were qualitatively and quantitatively described. This information was integrated in a facies analysis. The facies analysis allowed to identify and interpret 10 sedimentary facies, based on texture, structures and colors, which are grouped in four categories (Figs. 4-7): marls (massive and laminated marls), siliciclastic mudstones (dark fissile mudstones, red massive mudstones, and grey massive mudstones), mudstone-sandstone with heterolithic bedding (grey heterolithics with lenticular bedding, grey heterolithics with wavy bedding, and red heterolithics with wavy bedding), and finally, sandstones (cross-laminated sandstones and massive sandstones). Broadly speaking, marls and siliciclastic mudstones are interpreted as the result of settling from suspension, either in oxygen-rich (marls and red massive mudstones) or oxygen-depleted (dark fissile mudstones) sea floors. Heterolithic intervals with lenticular and wavy bedding represent recurrent alternation of settling and traction, the latter mostly as a result of ripple migration. Finally, the sandstones are interpreted as the product of wave-generated ripple migration (cross-laminated sandstones) or deposition under high-concentrated flows (massive sandstones). The ten recognized facies occur in a systematic order in the investigated succession. Therefore, three distinctive facies successions were defined (facies successions I, I, and III), and correlated when possible across subsurface or outcrop areas (Fig. 8). Facies successions I (4-25 m thick) comprises laminated and massive marls at the base, which grade vertically into red massive mudstones. Mudcracks are occasionally observed. Clay minerals are mostly illitic (illite and illite/smectite). This succession overlies the regional erosive karstic surface sculpted at the top of the Sierras Bayas Group (named Barker surface) and marks the resumption of mixed carbonate/siliciclastic sedimentation in the area. This facies succession is interpreted as deposited under supratidal conditions in a tidalflat depositional environment, probably under well oxygenated conditions. Facies succession II (0-150 m thick) conformably overlies the previous one in many of the investigated cored wells and is composed of dark fissile mudstones and massive grey siltstones, as well as grey heterolithics with lenticular and wavy bedding. In the fine fraction, clays are now dominated by chlorite and illite in similar proportions (Fig. 8b). This facies succession is interpreted to represent low-energy subtidal settings, likely with suboxic to anoxic bottom conditions. Facies succession III (up to 75 m thick) unconformably rests upon the previous, and represents an abrupt change to red heterolithics with wavy and flaser bedding, together with cross-laminated and massive, fine- to medium-grained sandstones (Fig. 8b). Mudcracks, scour marks and flutes are common in this succession. In these facies quartz and plagioclases are abundant, with subordinated clay minerals, which are composed mainly of illite and less proportion of chlorite. This succession is interpreted to represent subtidal to intertidal settings, probably with well-oxygenated substrates. The top of this succession has been removed by erosion both in subsurface and outcrops. The spatial (vertical and lateral) distribution of facies successions and their basal boundaries, together with the faults recognized by well correlation, provide the framework for the proposed tectono-sedimentary model for the investigated Neoproterozoic succession (Fig. 9). This begins with the stage I which coincides with the deposition of the facies succession I over the karstic surface of the top of Sierras Bayas Group. Then, the facies succession II is deposited conformably onto the previous one, and is related here to a sea level drop referred as stage II, which is followed by a transgressive event. Stage I was dominated by marly to clay-rich sedimentation under oxic conditions which turns to anoxic and purely siliciclastic during the stage II. At the end of the stage II the complete succession, including the Sierras Bayas Group strata, was affected by the reactivation of vertical to subvertical falls from the basement with modified the relief by uplift, followed by intense erosion and peneplanation. This period is defined as stage III. Finally, the stage IV is constituted by the deposition of the facies succession III in which the top is not preserved. The lithological and stratigraphic relationships defined in this contribution for the Neoproterozoic upper strata of the northwestern Tandilia System make necessary to postulate a new lithostratigraphic scheme for them. As mentioned before, the facies succession II is composed of up to 150 meters of mainly black shales and was almost unknown till the present study. This stratigraphic division is lithologically distinctive compared to facies successions I and III and is truncated at the top by an erosional unconformity. This interval is therefore proposed as a new formation here, complying the provisions of the article 28 of the Argentine Stratigraphic Code. This definition drives necessary the re-location of the facies succession I, not as the base of the Cerro Negro Formation, but as a new lithostratigraphic unit as well. In this sense, the facies succession I is here defined as Avellaneda Formation, while facies succession II is termed Alicia Formation (Fig. 10). The name Cerro Negro is here attributed solely to facies succession III, the reddish heterolithics that represent the uppermost part of the investigated strata. Moreover, these three lithostratigraphic units, conforming a discrete depositional record within a single basin, are grouped into a new lithostratigraphic unit defined as La Providencia Group (Fig. 10).
Keywords: Ediacaran, Río de La Plata craton, Alicia Formation, black shales